LSTM Network Hyperparameter Optimization for Stock Price Prediction Using the Optuna Framework - Edi Ismanto; Vitriani Vitriani (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2023)
This article has been retracted by the publisher.This article has been retracted because of misconduct and plagiarism. The document and its content have been removed from the Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, and reasonable effort should be made to remove all references to this article.